Factors associated with the reproductive health of women living with HIV in Iran - Sepideh Shikhansari; Zahra Bostani Khalesi; Enayatollah Homaei Rad (Elsevier, 2022)
Background: Insight on reproductive health status in women living with HIV is associated with improved psychological well-being, health behaviors, and physical wellness. The overall aim of this paper is to gain insight into the reproductive health of women living with HIV and related factors. Method: An analytical cross-sectional study was carried on women living with HIV (N = 112) attending high-risk behavior consultation centers in Rasht and Tehran, Iran. The sampling of respondents was in the form of consecutive and available. The data gathering including questionnaires that were divided into three parts: sociodemographic and health characteristics, reproductive behaviors information, and reproductive health assessment tool for women living with HIV. Result: The sub-dimension of responsible behavior received the highest total mean score (54.27 ± 22.18). The mean scores in the sub-dimension of coping with the diagnosis, life instability, disease disclosure, disease-related concerns, and support needs for self-care were 50.14, 49.23, 44.27, 40.08, 38.25, and 33.25 respectively. Conclusion: The results clearly showed that the reproductive health situation of women living with HIV needs particular attention. Strategic planning and context-specific interventions are needed to improve women's access and utilization of reproductive health services.